An atlas of metabolites driving chemotaxis in prokaryotes - Maéva Brunet; Shady A. Amin; Iurii Bodachivskyi; Unnikrishnan Kuzhiumparambil; Justin R. Seymour; Jean-Baptiste Raina (Nature Communications)
Abstract Chemicals inducing chemotaxis have been characterised for over 60 years across hundreds of publications. Without any synthesis of these scattered results, our current understanding of the molecules affecting prokaryotic behaviours is fragmented. Here, we examined 341 publications to assemble a comprehensive database of prokaryotic chemoeffectors, compiling the effect (attractant, repellent or neutral) of 926 chemicals previously tested and the chemotactic behaviour of 394 strains. Our analysis reveals that (i) not all chemical classes trigger chemotaxis equally, in particular, amino acids and benzenoids are much stronger attractants than carbohydrates; (ii) over one-quarter of attractants tested are not used for growth but solely act as chemotactic signals; (iii) the prokaryote’s origin matters, as terrestrial strains respond to 50% more chemicals than those originating from human or marine biomes; (iv) repellents affect cell behaviour at concentrations 10-fold higher than attractants; (v) the effect of large molecules and the behaviour of bacteria other than Proteobacteria have been largely overlooked. Taken together, our findings provide a unifying view of the chemical characteristics that affect prokaryotic behaviours globally.